Transformational leadership, emotional intelligence and organizational commitment: Pakistan’s services sector - Khan, Muhammad Ibrahim; Awan, Usama; Yasir, Muhammad; Mohamad, Noor Azmi Bin (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
This study investigates the moderating role of emotional intelligence in the relationship of transformational leadership and organizational commitment in the services sector of Pakistan. Data was collected from 267 respondents from different organizations in the services sector of Pakistan, i.e. telecom, banking, health and educational institutions. Transformational leadership was measured with a 20-item MLQ, multifactor leadership questionnaire, emotional intelligence was measured a 16-item scale (WLEIS, Wong and Law Emotional Intelligence Scale) and a 25- item scale (OCQ) measured the organizational commitment. The moderating role of emotional intelligence was assessed by creating an interaction term and was regressed with a dependent variable. This study provides managers with a new way to look at their employees attitudes, especially their commitment to their organization. Managers from the services sector of Pakistan should pay attention to their emotional intelligence competencies and should utilize these competencies for promoting a sense of respect among their employees, by valuing their cultural norms and thus enhancing their commitment to the organization. These results also identify the importance of training programmes for enhancing both leadership and emotional intelligence competencies. This is a comparatively easy and inexpensive way of gaining employee commitment as compared to some costly rewards and benefit packages.
Argumenta Oeconomica, 2014, Nr 2 (33), s. 67-92
Keywords: transformational leadership; emotional intelligence; organizational commitment; services sector; Pakistan